2012
DOI: 10.1111/j.1600-0579.2012.00753.x
|View full text |Cite
|
Sign up to set email alerts
|

A blended learning approach to teaching pre‐clinical complete denture prosthodontics

Abstract: Making use of the technologically advanced environment, the blended curriculum fostered student-focused learning to develop the didactic and laboratory skills necessary for competency in a pre-clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 11 publications
4
40
0
8
Order By: Relevance
“…Overall, there are limited research studies on perception of blended learning specifically in the dental curriculum, although there have been recent reports of positive outcomes on effectiveness, improved motivation, enhanced active engagement, and collaborative and interactive aspects of the utilisation of the flipped classroom, that are relevant as a context for this research study. [5][6][7][8][9][10][11] As new and innovative methods of learning are used in dental education, we also need novel and productive ways of assessing the students' perceptions of the learning experiences. We report here the first use of ICNDs to analyse dental students' percepts of a blended learning experience in dental education based on Likert-scale data.…”
Section: Blended Learning In Dental Educationmentioning
confidence: 99%
“…Overall, there are limited research studies on perception of blended learning specifically in the dental curriculum, although there have been recent reports of positive outcomes on effectiveness, improved motivation, enhanced active engagement, and collaborative and interactive aspects of the utilisation of the flipped classroom, that are relevant as a context for this research study. [5][6][7][8][9][10][11] As new and innovative methods of learning are used in dental education, we also need novel and productive ways of assessing the students' perceptions of the learning experiences. We report here the first use of ICNDs to analyse dental students' percepts of a blended learning experience in dental education based on Likert-scale data.…”
Section: Blended Learning In Dental Educationmentioning
confidence: 99%
“…[18][19][20] Kavadella et al 20 evaluated the educational effectiveness of blended lessons with conventional lessons. They found that blended learning is well evaluated by undergraduate students.…”
Section: Discussionmentioning
confidence: 99%
“…In another study by Bains et al, 19 blended learning was more effective and accepted compared with RLE or face-to-face learning alone. The blended curriculum with studentfocused learning to create didactic and laboratory skills was approved at the end of the study of Faraone et al, 18 in which a preclinical complete denture prosthodontics lesson was tested. Future studies are needed in which the blended, HCE, and RLE methods are compared for deep learning in orthodontics, both in practical work and in diagnosing clinical situations.…”
Section: Discussionmentioning
confidence: 99%
“…This method also enables efficient use of time (Camargo et al, 2011;Faraone, Garrett & Romberg, 2013;Maresca et al, 2014), individualizes the educational process, and allows the students to work at their own pace and to repeat the educational program as much as needed while reducing the cost required for education (Al-Jewair et al, 2010;Catteau et al, 2013;Maresca et al, 2014). In many countries, 4 or 5-year dental educational period starts with theoretical courses and terminates with practical ones.…”
Section: Introductionmentioning
confidence: 99%